A universal optoelectronic imaging platform with wafer-scale integration of two-dimensional semiconductors - Xinyu Wang; Die Wang; Yuchen Tian; Jing Guo; Jinshui Miao; Weida Hu; Hailu Wang; Kang Liu; Lei Shao; Saifei Gou; Xiangqi Dong; Hesheng Su; et al. (Chip)
Photodetectors (PDs) are crucial in modern society as they enable the detection of a diverse range of light-based signals. With the exponential increase in their development, materials are being used to create a wide range of PDs that play critical roles in enabling various applications and technologies. Image sensor technology has been hindered due to the lack of a universal system that can integrate all types of PDs with silicon-based readout integrated circuits (ROICs). To address this issue, we conducted experiments adopting two-dimensional materials as an example. High-performance MoS2-/MoTe2-based PDs were fabricated in the current work and the most suitable ROICs were identified to pair with them. This established a solid foundation for further researches in the field of image sensors. We developed and implemented a versatile testing system that uses a printed circuit board to connect the PD and ROIC. After the ROIC generates the sampled signal, it is collected and processed by algorithms, which overcome device uniformity limitations and produce a high-quality image that is visible to the naked eye. This universal system can be used with a wide range of PD and ROIC types made from different materials, making it highly convenient for diverse testing applications and the development of diverse image sensor types. This robust new platform is expected to spur further innovation and advancements in this rapidly developing field.